Aktas: research and materials - Khabdulina Марал (Turkic Studies Journal, 2025)
The monograph presents materials from two archaeological sites in Eastern Zhetysu, investigated by K.A. Akishev in the 1960s: the ancient Wusun settlement Aktas-2 and the Xiongnu burial ground Aktas I. These sites from the first half of the 1st-millennium AD are located along the Kegen River in the Kurailly Gorge of the Ketmen Mountains. Previously unpublished, these materials remained in the scholar’s archive as field photographs and drawings, documented by mid-20th-century standards. Publishing the monograph required extensive modernization and preparation of the materials for contemporary research. Structured into an introduction, three chapters, and a conclusion, the monograph explores key theoretical issues in Wusun and Xiongnu archaeology. The introduction provides a historical overview of research in Eastern Zhetysu, highlighting the diversity of its archaeological sites and the region’s significant settlement during both the ancient and medieval periods. The first chapter examines the Ketmen geosystem’s environment, crucial for understanding ancient economies. The monograph’s significance lies in detailed interpretation of excavation records through K.A. Akishev’s theoretical contributions to nomadic studies. The second chapter provides archaeological evidence of settlement and agriculture among the ancient Wusun, including remains of vegetable gardens and irrigation systems. These findings, originally documented in the 1960s, are enriched by modern excavations of settlements and kystau nomadic sites in Kazakhstan and neighboring regions. The third chapter analyzes materials from the Aktas I burial ground, associated with the common population of the late Wusun and Xiongnu periods. The significance of this analysis lies in its contribution to the study of Xiongnu cultural characteristics. The examination of the Aktas I burial ground has facilitated the identification of a complex of ethnically formative features within the Xiongnu funeral rites. The conclusion addresses theoretical issues from studying the Aktasty monument complex. A key result of researching the Aktas-2 settlement is revising the concept of continuous nomadism and the assumption that nomads avoided agriculture. The study establishes the coexistence of agriculture and cattle breeding as a fundamental methodological principle in analyzing archaeological and historical sources. Additionally, the monograph provides valuable insights into Xiongnu archaeology and the ethnic dynamics of the Great Migration period.